PENERAPAN MODEL INKUIRI TERBIMBING (GUIDED INQUIRY) PADA PEMBELAJARAN FISIKA MATERI LISTRIK DINAMIS DI SMK - Qurroti A’yunin; Indrawati Indrawati; Subiki Subiki (JURNAL PEMBELAJARAN FISIKA, 2017)
This research related to the implementation of Guided Inquiry LearningModel of dynamic electric of physics material at SMK. The purpose of this researchwere: 1) to describe the learning activities in the experimental class; 2) to analysethe effect of Guided Inquiry Learning Model on the students’ learning result; and 3)to describe the relationship between the activity and the achievement ofexperimental class. The type of this research was experimental research. Thesamples of this research were the students’ of 11th TKJ.1 as control class and 11thIL.2 as experimental class at SMKN 2 Jember.The Design of this research wasposttest-only control design. Moreover the data collection methods were; test,observation, documentation, and interviews. Additionally, the data analysed were;Independent-sample T-test (parametric test) or the Mann-Whitney test (nonparametrictest) as the comparison test, while Test-Product-Moment Correlation-Pearson as the correlation test. The first research result showed that the average oflearning activities in experimental class based on observation and documentationduring the learning process was 82.31%, active criteria. The largest percentage ofmotor-activities was 90.95% but the lowest oral-activities was 76.34%. Meanwhile,the second research result showed that there was a significant difference ofcognitive, psychomotor, and affective of the control and experimental class students’achievement. The Sig.(1-tailed) value gain was lower than α=0,05, that was 0.000(cognitive-Independent-Sample-T- test), 0.000 (psychomotor-Mann-Whitney-Test)and 0.012 (affective-Independent-Sample-T-test). So that the model of GuidedInquiry Learning had a significant effect on the students’ achievement in dynamicelectric of physics material at SMK (H0 rejected, Ha accepted ). Moreover the thirdresearch result showed the correlation coefficient value between the activity andachievement as 0.520, so there was a correlation between them. The criteria ofcorrelation was medium with positive direction. Sig.(2-tailed) value was 0.003 or <0.05, so there was a significant relationship between the activity and theachievement on the experimental class.